Developmentally and Trauma-Sensitive Courtrooms. (November 2019) - Crenshaw, David A.; Stella, Lori; O'Neill-Stephens, Ellen; Walsen, Celeste
Courtrooms in the United States whether family court or criminal court fall far short of being either developmentally or trauma sensitive. While there is growing recognition that vulnerable child witnesses are at risk of retraumatization by court procedures and some judges have used their discretionary powers to render courtrooms less toxic to children, the system was designed by adults for adults, and certainly not for children. The court process especially in criminal trials does not typically take into account the developmental constraints of children nor do they fully understand trauma in children and the risks to testifying child witnesses. Humanistic psychology has long stood for social justice and compassion toward our most vulnerable humans, especially children, but the long and slow-to-change traditions of the court system in the United States creates an environment that is inhospitable to children and even older victims as illustrated by the low rate of prosecutions in rape cases. This article outlines the distressing conditions that await child victims/witnesses in this country in comparison with other developed countries and an innovative, out-of-the box solution that does not interfere with the rights of the accused.